NEW GENERA AND SPECIES OF THYSANOPTERA – THRIPIDAE FOR CUBA - Rodríguez-Romero, A.; Suris, Moraima (Revista de Protección Vegetal, 2013)
With de aim of updating the trips faune in the province of Guantánamo, the genera Cercyothrips Morgan, Enneothrips Moulton, Stenchaetothrips Bagnall and Psectrothrips Hood are reported for the first time in Cuba as a result of successive samplings at different locations. Among the new species found were Cercyothrips galbinus Hood on Acacea farmeseana L. Willd in the municipality of El Salvador; Enneothrips gustativiae Hood, on Sambucus canadensis L. and Sesuviun portulacastrum L. in the localities of Arenal and Piedra la Vela respectively, belonging to the municipality of Yateras; Psectrothrips palmarae Mound and Marullo on Tabebuia bibracteolata Griseb. Britton in Piedra la Vela; Tabebuia angustata Britton in the locality of La Mesita, Baracoa; and Stenchaetrothrips minutes Deventer on Echinochloa cruz-galli L. in the locality of Bayate, municipality of El Salvador.